Musculoskeletal Disorders pada Pekerja Cleaning Service RSUD Kota Semarang - Erik Pratama; MG. Catur Yuantari (VISIKES: Jurnal Kesehatan Masyarakat, 2016)
Musculoskeletal disorder is the pains on muscle of skeletal that can be felt by people begin from medium to very sick pains. Based on the initial survey, cleaning services employee had musculoskeletal disorders on back, neck, hands and foot. The purposed of this study was to analyze factors correlated to cases of musculoskeletal disorders on cleaning services employee in Semarang district hospital.The study was explanatory research with cross sectional approach. The instrument was interview guidelines, data clollected by observation and interview. The number of sample was 44 people. Data was analyzed by pearson correlation and rank spearman. Result showed that musculoskeletal disorder happened on right hand (100%),Â  left hand (93.2%), right foot (70.5%), left foot (68.2%) and back pain (63.6%). Majority of the cleaning services employee 38 people (86.4%) suffered from middle musculoskeletal disorder. There was correlation between nutritional status and musculoskeletal disorder and there was no correlation between age, gender, lenght of work, work period, work attitude, smoking behavior, exercise and recurrent activities and musculoskeletal disorder.The suggestion is hospital has to standardize the tool of cleaning service to prevents musculoskeletal disorders.Keywords: musculoskeletal disorder, cleaning services, nutritional status.